The Effectiveness of Life Skills-Based Information on Increasing Self-Confidence and Career Planning - Hidayahtulloh, Puji Deputri Nur; Izzaty , Rita Eka (Universitas Ahmad Dahlan, 2024)
The problems that students experience most common today are a lack of self-confidence and a lack of career planning. This study is quantitative, using a quasi-experimental design with a non-equivalent control group design, aiming to determine the effectiveness of life skills-based career information services for high school students. The respondents in this study were twelfth-grade high school students, with a total of 72 students selected using simple random sampling. The instrument used in this study was a questionnaire. The data analysis techniques used were descriptive statistical analysis, normality tests, homogeneity tests, and paired sample t-tests for testing the effective contribution. This Life Skills-Based Career Information Service is effective and proven to be significant. These results suggest that career information services need to be provided to students so that they can determine career choices according to their potential.